2010
DOI: 10.3109/09638281003649912
|View full text |Cite
|
Sign up to set email alerts
|

Musculo-skeletal pain, quality of life and depression in mothers of children with cerebral palsy

Abstract: Deterioration of MH in mothers with cerebral palsied child may be causing them to experience more LBP. Experience of increased LBP causes deterioration of health-related QoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
61
1
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 24 publications
9
61
1
4
Order By: Relevance
“…In literature, the caregivers of children with severe clinical impairments, especially with regard to motor function, are more likely to have greater physical and mental distress than other caregivers [17][18][19][20][21]. In addition, caregivers' QoL was significantly affected by the motor function of children with CP in this study.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…In literature, the caregivers of children with severe clinical impairments, especially with regard to motor function, are more likely to have greater physical and mental distress than other caregivers [17][18][19][20][21]. In addition, caregivers' QoL was significantly affected by the motor function of children with CP in this study.…”
Section: Discussionsupporting
confidence: 48%
“…The scores for functional capacity, vitality, general health status, and emotional states were significantly lower and the pain domain was higher than in the primary caregivers of children with CP compared to the control group. The other Turkish study evaluated the QoL of 40 mothers of children with CP, compared to 44 mothers of children with other problems such as general deconditioning, fever, or diarrhea using the SF-36 and GMFCS [21]. The overall scores of the SF-36 domains were significantly lower in mothers of children with CP than in the non-chroni-cally diseased group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mothers of children with diffi culties had signifi cantly more negative emotional conditions and more symptoms of depression 14 because they had lack of positive feelings such as joy, pleasure, loveliness, pride and fulfi llment of hope 20 . It was found that over years, parents of children with cerebral palsy, in comparison to parents of healthy children, more often complained of experiencing severe and chronic stress, emotional and cognitive problems, as well as numerous somatic diffi culties [21][22][23][24][25] . Mothers of children with cerebral palsy are exposed to psychological pressure, are under the impact of stress and depression, are worried for their child's future, most of their time spend on the child's nutrition, health, treatment, rehabilitation, are subjected to financial burdens (transport, child care, therapy, providing adaptive equipment and modifi cations in the house) 26 , which causes decline in the quality of life of mothers (both physically and psychologically), whereas mothers of healthy children have more free time, are more involved in social activities, entertainment and work 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Parents of children with cerebral palsy (CP) experience physical and social difficulties. The family may lack a sense of wellbeing (10)(11)(12) and parents can experience musculoskeletal pain (13). Siblings of children with the condition may also be affected (14,15).…”
Section: Introductionmentioning
confidence: 99%